Teacher Education in the North-eastern Region of India An Evaluation - Das, B.C. (JOURNAL OF INDIAN EDUCATION, 2017)
In this descriptive research study, an attempt has been made to investigate into the organisation of secondary teacher education programmes w.r.t. physical facilities, admission and selection procedures, curricular and co-curricular activities, methods and aids used, practice teaching, research facilities, finance, innovative practices, core staff, evaluation procedure and overall assessment of the programme in the North-eastern region of the country. This follows identifying the difficulties faced while organising such programmes and at the end, suggestions have been given for the qualitative improvement of the secondary teacher education programmes in this region.